An integrated assessment of China's South—North Water Transfer Project. (23rd October 2019) - Rogers, Sarah; Chen, Dan; Jiang, Hong; Rutherfurd, Ian; Wang, Mark; Webber, Michael; Crow‐Miller, Britt; Barnett, Jon; Finlayson, Brian; Jiang, Min; Shi, Chenchen; Zhang, Wenjing
Abstract: China's South–North Water Transfer Project (SNWTP) is a vast and still expanding network of infrastructure and institutions that moves water from the Yangtze River and its tributaries to cities in North China. This article aims to assess the SNWTP's impacts by beginning to answer seven questions about the project: How is the management of the SNWTP evolving? What are the problems to be resolved when managing SNWTP water within jurisdictions? What are the status and management of water quality in the SNWTP? What are the consequences of resettlements caused by the SNWTP? How is increased water supply affecting regional development? Is the SNWTP achieving its stated environmental goals? What are the sustainability credentials of the SNWTP? Drawing on primary and secondary data, the article demonstrates both that the opportunities and burdens characterising the project are highly uneven and that management systems are evolving rapidly in an attempt to enforce strict water quality targets. Furthermore, while the SNWTP may be helping to resolve groundwater overexploitation in Beijing, it is highly energy intensive, raising questions about its sustainability. Our analysis highlights the need to continue to interrogate the socio‐economic, environmental, and political implications of such schemes long after they are officially completed.